Estimation of phenolic acids in cinnamon, clove, cardamom, nutmeg and mace by high performance liquid chromatography - BANDYOPADHYAY, PRASAD S VARIYAR, CHIRANJIB (Journal of Spices and Aromatic Crops, 1995)
Phenolic acids of five commercially important spices, namely, cinnamon, clove, cardamom, nutmeg and mace were quantitated by high performance liquid chromatography using external standard method. Protocatechuic acid was the predominant phenolic acid in cinnamon bark, while gallic acid dominated in clove buds. The major phertolic acids in cardamom seeds and nutmeg were caffeic acid + vanillic acid while ferulic acid and synapic acid predominated in mace.